The Renewal Officinal Pilot Models of Varieties of Long-fibred Flax and Crown Flax (Linum usitatissimum L., Linum humili Mill.) - Н. П. Костенко (Plant Varieties Studying and Protection, 2012)
The article represents results of renewal to officinal pilot models of varieties of long-fibred flax and crown flax to bring in to high-yielding properties to the environmental conditions of areas of Forest Ukraine. There brief descriptions of comparative evaluation of identifications morpho-biological indications plants of varieties to place on control pilot models with plants of varieties to place on standard models. There are installed the authentic of descriptions to officinal pilot models of varieties.